Pembangkit Listrik Tenaga Surya Di Waisai Kabupaten Raja Ampat Provinsi Papua Barat - Yunus Fa Bate; Stefany Margareta Martono (LPPM Poltek ST Paul, 2019)
The electrical energy needs become one of the basic needs of both people who live in cities and people who live in villages. The government continues to strive to provide these electricity needs so that the electrification ratio and electricity villages in Indonesia can be gradually increased. Based on data from the Directorate General of Electricity and Energy Utilization of the Ministry of Energy and Mineral Resources in 2017, parts of western Indonesia ranging from the Aceh Special Region to Sulawasi, the electrification ratio reaches an average of above 70%. For the province of West Papua, has an electrification ratio of 82.7% but there is an imbalance in terms of equity where the ratio of electrified villages is only 54.47%. West Papua are rural and archipelago with geographical conditions making mobilization of tools very difficult. To increase the ratio of electricity villages, one solution that can be done is to optimize the use of natural resources for construction of electricity generation. The potential of natural resources in West Papua especially in the Waisai region of Raja Ampat Regency is abundant solar energy both in the intensity of solar radiation and the length of time of irradiation due to geographical location located on equator. The research was carried out experimentally by making solar power plants using photovoltaic 50 Wp to obtain empirical data that provides information on the potential parameters of solar power plants. The results obtained indicate that in Waisai Raja Ampat the maximum radiation intensity can reach 1101.2 W / m2, the maximum input power and maximum power output of photovoltaic cells are 339.9404 Watt and 30.46640 Watt and maximum efficiency reaching 9.26%. Based on these empirical data, the prospect of utilizing photovoltaic type solar power plants in Waisai Raja Ampat Regency is very good and appropriate.